(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe and compare the disease model of inpatients at Bac Thang Long Hospital during the periods 2018 – 2019 and 2022 – 2023. Subjects and Methods: Cross-sectional descriptive study. All inpatients at Bac Thang Long Hospital from 01/01/2018 – 31/12/2019 and 01/01/2022 – 31/12/2023, with complete medical records and diagnoses coded according to ICD-10, were included. Results: Inpatients at Bac Thang Long Hospital during 2018 – 2019 and 2022 – 2023 were mainly adults engaged in manual labor and children under 6 years old. Over 90% of patients had medical examinations covered by health insurance. More than 40% of patients resided outside Dong Anh district. The highest number of inpatients was admitted to the pediatric department, while the ophthalmology department had the lowest admissions. The highest incidence was found in Chapter X – Respiratory diseases, Chapter XI – Digestive system diseases, and Chapter IX – Circulatory system diseases. In both periods, bacterial pneumonia, unspecified (J15), neonatal feeding problems (P92), single liveborn by cesarean delivery (O82), essential (primary) hypertension (I10), and other bacterial intestinal infections (A04) remained among the top ten most common conditions. There were some changes in disease model in the 2022 – 2023 period compared to 2018 – 2019. Conclusion: In the period 2022 - 2023, there was an increase in respiratory infections and strokes. Based on the observed disease model, appropriate planning is needed to ensure adequate healthcare services for the population’s needs.